Estimation of subsurface carbon stock of mangrove on Takari Beach, Rebo Village, Merawang District, Bangka Regency - Farhaby, Arthur Muhammad; Henri, Henri; Putri, Lizha Dwi Mulya; Alissyah, Radiva Putri; Ardiyansah, Feri; Simatupang, Mikha Josevan; Pasaribu, Pilip Noel Parnangkok; Adha, Muhammad Thoriq (Bioma : Berkala Ilmiah Biologi, 2025)
The Bangka Belitung Islands Province has a mangrove ecosystem covering an area of 273,692.81 hectares. These ecosystems play a crucial role in mitigating greenhouse gas emissions through the sequestration mechanism, which involves absorbing carbon from the atmosphere and storing it in the form of biomass. Human activities around these areas, such as the flow of tailings from artisanal mining (TI), have caused damage to these ecosystems, leading to a reduction in one of the primary carbon dioxides (CO2) absorbers. This study aims to support the sustainable management of mangrove conservation areas in efforts to reduce the impact of global warming. Sampling stations were determined using purposive sampling, with the collection of substrate carbon, biomass, and carbon samples, as well as water quality parameters at Takari Beach. The results showed that the water temperature was 28°C, salinity ranged from 25 to 27 ppt, and pH ranged from 5 to 8,5. Four mangrove species were found at two stations: Rhizophora mucronata, Rhizophora apiculata, Sonneratia alba, and Lumnitzera littorea, totaling 185 trees. The mangrove biomass was measured at 27,10636 tons/ha, and the below-ground carbon stock was recorded at 12,74 tons/ha.